2006
DOI: 10.1111/j.1440-1673.2006.01565.x
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia can cause 111Indium octreotide uptake

Abstract: An 18-year-old woman underwent an (111)In octreotide scan for evaluation of a possible insulinoma. This showed mildly increased radiopharmaceutical uptake involving the right lung base. The patient reported a productive cough for 5 days before the octreotide scan. A chest radiograph was taken, which showed increased airspace opacification in the right lower lobe, corresponding to the uptake seen on the octreotide scan. After a course of oral antibiotics, the patient's chest symptoms improved and the radiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Normal physiologic distribution of In-111 octreotide includes faint visualization of thyroid, pituitary gland and marked increased uptake in the liver, spleen, kidneys and bladder. Although rarely encountered, false-positive studies have been reported due to increased activity at nonmalignant pathologies such as Paget’s disease, parathyroid adenoma, cholecystitis, thrombus, abscess, infection, pulmonary fibrosis, pleural plaques and uterine myomas ( 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ). Only a few cases in the literature have reported increased In-111 octreotide activity in the gallbladder ( 10 , 11 , 12 , 13 , 14 ).…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Normal physiologic distribution of In-111 octreotide includes faint visualization of thyroid, pituitary gland and marked increased uptake in the liver, spleen, kidneys and bladder. Although rarely encountered, false-positive studies have been reported due to increased activity at nonmalignant pathologies such as Paget’s disease, parathyroid adenoma, cholecystitis, thrombus, abscess, infection, pulmonary fibrosis, pleural plaques and uterine myomas ( 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ). Only a few cases in the literature have reported increased In-111 octreotide activity in the gallbladder ( 10 , 11 , 12 , 13 , 14 ).…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…in their study have reported a case of an 18-year-old woman which underwent an 111 In octreotide scan for evaluation of a possible insulinoma. [8] Scan showed mildly increased radiopharmaceutical uptake involving the right lung base. On closer inquiry, the patient reported a productive cough for 5 days before the octreotide scan.…”
Section: Discussionmentioning
confidence: 99%
“…Patient was diagnosed with community-acquired pneumonia. [8] Uptake seen in inflammatory conditions is probably the result of tracer binding by somatostatin receptors on the inflammatory leukocytes…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSR-positive immune cell infiltration of lung parenchyma may cause an increased radioanalog uptake in pulmonary inflammations secondary to exposure to infectious agents and without granulomatous evolution as well (115,116). This last setting should be taken into consideration to avoid false positive interpretations when SRS is performed in the suspicion of non-infectious pulmonary diseases (17).…”
Section: © 2 0 0 7 E D I T R I C E K U R T I Smentioning
confidence: 99%